The Diffusion of the Topic Carbon Nanotube Over the Universe of Subjects: A Statistical Analysis - Paul, Swapan; Dutta, Bidyarthi (Journal of Data Science, Informetrics, and Citation Studies)
The diffusion is basically a physical process, which is essential in many physical, chemical and biological phenomena. The diffusion of knowledge refers to the interchange and propagation of knowledge through different media, or the transfer of knowledge from one subject to another. The concept of diffusion or dissemination of knowledge eventually gave rise to the concept of the diffusion of any specific topic over the universe of subject. In this paper, the growth of literature and the diffusion of the multidisciplinary topic “Carbon Nanotube” have been discussed since the year 1992 to 2022. The analysis of growth of literature shows the topic “Carbon Nanotube” follows logistic growth pattern over the last thirty years, which accords De Solla Price’ theory. The topic “Carbon Nanotube” was born in the subject ‘Physics’ and then gradually became relevant or contextual with other subjects in due course of time like material science, chemistry, chemical engineering, environmental science, engineering etc. The core journals published the papers on ‘Carbon Nanotube’ had also been changed over the stipulated time span of thirty years. The diffusion phenomenon has been proved here by the analysis of correlation coefficients between the ranks of the core journals and the ranks of the associated subjects. The proof of diffusion phenomenon of a specific topic over several broad subjects’ fields by correlation analysis is a new technique introduced here. This technique can be applied for studying diffusion of other multidisciplinary topics over various broad subjects.
Keywords: Universe of Subject; Diffusion; Knowledge Diffusion; Carbon Nanotube; Diffusion by Correlation Analysis.